2006
DOI: 10.5032/jae.2006.04039
|View full text |Cite
|
Sign up to set email alerts
|

Agriscience Teachers’ Attitudes Toward Implementation of Content Area Reading Strategies

Abstract: As part of a larger study, four agriscience teachers were interviewed about their perceptions, attitudes, and challenges with implementing content area reading strategies (CARS) in secondary agriscience. In the larger study, two of the teachers implemented a treatment of systematic, planned, and thoughtful CARS in two agriscience courses, while the other two teachers provided the comparison of teaching their “normal” routine of instruction. Prior to the study, agriscience teachers implemented few or no CARS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Spencer, Carter, Boon, and Simpson-Garcia (2008) concluded that research findings have proven the great significance of explicit strategy instruction in developing reading skills. Additionally, Park and Osborne (2006) have cited numerous studies showing that instruction using reading strategies is the most effective means of increasing student comprehension and developing skilled readers.…”
Section: Journal Of Language Teaching and Researchmentioning
confidence: 99%
“…Spencer, Carter, Boon, and Simpson-Garcia (2008) concluded that research findings have proven the great significance of explicit strategy instruction in developing reading skills. Additionally, Park and Osborne (2006) have cited numerous studies showing that instruction using reading strategies is the most effective means of increasing student comprehension and developing skilled readers.…”
Section: Journal Of Language Teaching and Researchmentioning
confidence: 99%
“…Within agricultural education, research has identified agriculture teachers often neglect literacy integration in favor of the hands-on learning opportunities prevalent in agricultural education (Park & Osborne, 2006b). However, agriculture teachers still perceive teaching literacy concepts as a positive endeavor with the potential to benefit their students (Park & Osborne, 2006b). The research in agricultural education exemplifies the disconnect identified previously; teachers perceive literacy integration as positive yet fail to continually reinforce literacy skills and concepts within their classrooms.…”
Section: Content Area Literacymentioning
confidence: 99%
“…While research identifies the importance of the agriculture teacher in the success of their students learning math and ELA content, there exists a dearth of studies in agricultural education exploring agriculture teachers' perceptions of math and ELA integration, even outside the context of the CCSS (Park & Osborne, 2006). Although agricultural education teachers' attitudes toward the CCSS have not previously been explored, research outside of agricultural education has investigated the topic.…”
Section: Introduction and Theoretical Frameworkmentioning
confidence: 99%